Combining immune-related adverse events and inflammatory profiles enhances prognostic accuracy in metastatic melanoma under PD-1-based therapy - Garmpis, Dionysios; Hidalgo-Gadea, Guillermo; Mauch, Cornelia; Tietze, Julia K.; Franklin, Cindy (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) have improved outcomes in advanced melanoma, yet predictive biomarkers for treatment response and survival remain limited. Immune-related adverse events (irAEs) are frequent during ICI therapy and have been associated with improved outcomes, while baseline inflammatory markers—such as C-Reactive protein (CRP) and neutrophil-to-lymphocyte ratio (NLR)—often predict poor prognosis. However, no study to date has systematically integrated irAE characteristics and blood-based inflammation profiles to evaluate their combined prognostic value across different therapy lines.MethodsWe retrospectively analyzed 231 patients with unresectable stage IIIC–IV melanoma treated with PD-1-based ICIs at the University Hospital Cologne (2015–2021). Patients were stratified into first-line (n=149) and higher-line (n=82) groups. We assessed the occurrence, number, type, and severity of organ-specific and non-specific irAEs, and correlated these with progression-free survival (PFS) and overall survival (OS) alongside baseline hematological markers (CRP, neutrophils, lymphocytes, lymphocyte-to-monocyte ratio (LMR), NLR) using multivariate Cox regression.ResultsAcross both therapy lines, the occurrence, higher number, and moderate severity (CTCAE I–III) of organ-specific irAEs independently predicted longer PFS and OS, whereas high-grade irAEs (≥IV) were associated with worse OS. In first-line therapy, ≥2 irAEs conferred markedly prolonged PFS (HR 0.49; p=0.007) and OS (HR 0.53; p=0.040). Elevated CRP and neutrophils predicted shorter survival, while higher lymphocyte counts and LMR were favorable; CRP emerged as the most consistent independent prognostic biomarker. Eosinophil counts predicted both irAE development and improved survival in univariate analyses only. Combining irAEs with CRP and lymphocyte-based markers improved PFS prediction, particularly in first-line therapy.ConclusionIntegrating irAE characteristics with baseline inflammatory biomarkers enhances prognostic stratification in ICI-treated melanoma, especially in first-line settings. Moderate irAEs appear to reflect beneficial immune activation, whereas high-grade events may compromise outcomes. CRP and lymphocyte-based indices provide additive value and should be considered in future biomarker-driven patient selection and monitoring strategies.